2020
DOI: 10.1093/ije/dyaa241
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammatory regulators and risk of Alzheimer’s disease: a bidirectional Mendelian-randomization study

Abstract: Background Systemic inflammation has been suggested to be associated with Alzheimer’s-disease progression, although whether it is a cause or a downstream effect is still controversial. This study aims to assess the effect of systemic inflammatory regulators on Alzheimer’s disease within a bidirectional Mendelian-randomization design. Methods Genetic associations with Alzheimer’s disease were obtained from the largest and most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…found that none of the genetically predicted 41 systemic inflammatory regulators were associated with the risk of AD. Conversely, AD was associated with five systemic inflammatory regulators, which implied that genetically predicted systemic inflammation may be a downstream effect of AD or a consequence of comorbidity factors ( 27 ). As inflammation is the core pathological mechanism of IBD, we should further verify whether AD leads to an increased risk of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…found that none of the genetically predicted 41 systemic inflammatory regulators were associated with the risk of AD. Conversely, AD was associated with five systemic inflammatory regulators, which implied that genetically predicted systemic inflammation may be a downstream effect of AD or a consequence of comorbidity factors ( 27 ). As inflammation is the core pathological mechanism of IBD, we should further verify whether AD leads to an increased risk of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…To address the aforementioned issues, Katan et al (1986) introduced the concept of Mendelian randomization (MR) in 1986. MR is an epidemiological approach for investigating whether a causal effect exists between exposures and outcomes by using genetic variants as instrumental variables (IVs) ( Yeung & Schooling, 2021 ). This approach uses genetic variants that depend on strongly associated single-nucleotide polymorphisms (SNPs) from genome-wide association studies (GWASs) and makes use of the random classification of alleles during gametogenesis, which is similar to randomized clinical trials ( Qu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, Mendelian randomization (MR) is an alternative approach using genetic instruments that are randomly allocated at conception as a proxy of exposure to infer the causality of life-long exposure on disease [14]. Three recent MR studies on inflammatory markers and Alzheimer's disease (AD), the most common type of dementia, have yielded inconsistent results [15][16][17]. Despite being done in large populations, these studies could still suffer from limited power caused by a limited number of cases.…”
Section: Introductionmentioning
confidence: 99%